Research advances of Hippo signaling pathway and acute kidney injury - Guo Wen-li; Wu Wei-hua; Ou San-tao (Linchuang shenzangbing zazhi)
Acute kidney injury（AKI）is an acute and critical illness with high morbidity and mortality.As a serious threat to human health, it has become a global public health hazard.The pathogenesis of AKI is not fully elucidated and there is still a lack of effective treatment.Hippo signaling pathway is an essential signal transduction pathway involved in regulate cell proliferation, differentiation and apoptosis.It has been proved to be associated with the occurrence and development of tumors, vascular remodeling of cardiovascular diseases and proliferation and differentiation of stem cells.Recently it has been confirmed that Hippo signaling pathway plays an important role in AKI as well.This review described Hippo signaling pathway and its role in the development of AKI provide new insights for preventing and treating AKI.